EKSPLORASI ETNOMATEMATIKA PADA PERMAINAN PINDAN - Apriosa, Kurnia Dwi; Sholikin, Nur Wiji (AL JABAR: Jurnal Pendidikan dan Pembelajaran Matematika, 2025)
This research aims to explore the ethnomathematics values contained in the traditional pindan game in Jrebeng Kidul Village, Probolinggo, East Java. Pindan is a local game that not only functions as entertainment, but also as a means of character and social education for children and teenagers. Through a descriptive qualitative approach, this research identifies mathematical concepts such as patterns, logic, speed and dexterity that emerge in the dynamics of the game. The findings show that the integration of local cultural elements in mathematics learning can strengthen students' understanding of abstract concepts, as well as foster critical and analytical thinking skills. Apart from that, this game plays an important role in strengthening social relations between residents and preserving local wisdom in the midst of globalization which is shifting the popularity of traditional games. This research recommends developing a curriculum based on local culture to increase the relevance of mathematics learning in students' daily lives.